2014
DOI: 10.1017/s1041610213002561
|View full text |Cite
|
Sign up to set email alerts
|

The Koori Growing Old Well Study: investigating aging and dementia in urban Aboriginal Australians

Abstract: This paper details our protocol for a population-based study in collaboration with local Aboriginal community organizations. The study will provide the first available prevalence rates for dementia and cognitive impairment in a representative sample of urban Aboriginal people, across city and rural communities, where the majority of Aboriginal Australians live. It will also contribute to improved assessment of dementia and cognitive impairment and to the understanding of social determinants of successful aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 26 publications
1
71
0
Order By: Relevance
“…The Koori Growing Old Well Study in urban and regional NSW (Radford et al 2014) found that the dementia rate in Indigenous communities was three times that of nonIndigenous communities. Indigenous Australians face a 'cascade' of risk factors across the life-span, including low birth weight, removal from family, education, head injuries, alcohol misuse, smoking and inactivity.…”
Section: Population Findingsmentioning
confidence: 99%
“…The Koori Growing Old Well Study in urban and regional NSW (Radford et al 2014) found that the dementia rate in Indigenous communities was three times that of nonIndigenous communities. Indigenous Australians face a 'cascade' of risk factors across the life-span, including low birth weight, removal from family, education, head injuries, alcohol misuse, smoking and inactivity.…”
Section: Population Findingsmentioning
confidence: 99%
“…Urban/regional populations differ from remote populations in that they are more likely to have been exposed to formal education systems, have higher levels of education and literacy, and speak English as a first or primary language [22]. Therefore, standard cognitive tools such as the MMSE and RUDAS should be appropriate for use in urban Aboriginal populations, along with the culturally specific KICA-Cog (adapted for urban settings).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, standard cognitive tools such as the MMSE and RUDAS should be appropriate for use in urban Aboriginal populations, along with the culturally specific KICA-Cog (adapted for urban settings). A primary aim of the epidemiological Koori Growing Old Well Study (KGOWS) [22] was to assess the relative performance of these standard (MMSE and RUDAS) and adapted (KICA-Cog) cognitive screening instruments for the diagnosis of dementia and cognitive impairment in the urban/regional Aboriginal population of Australia. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A key component of this health disparity is the notably higher prevalence rates of dementia now documented for younger as well as older Indigenous Australians, and increasingly men as well as women. 2,[4][5][6][7][8] This growing burden of disease has been proposed to reflect complex and intergenerational health risk factors. Studies document how Australia's Indigenous peoples are at greater risk for chronic diseases that increase susceptibility to dementia, including Type 2 diabetes, cardiovascular disease and obesity.…”
mentioning
confidence: 99%
“…5,[18][19][20]24,25 These sessions gathered information to guide future community-based training and education. The 38 women and 12 men who participated ranged in age from 22 to 85 years (M = 46.4 ± 16).…”
mentioning
confidence: 99%